Preparation method of flame-retardant adhesive film, flame-retardant adhesive film and use method of flame-retardant adhesive film
Through the preparation of POE-PPZ branch polymer glue film, the problem of perovskin solar cells damage at high temperature and insufficient traditional glue film performance, and realizes low-pressure temperature packaging and long-term stability improvement.
Patent Information
- Application Number
- CN202411510927.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The long-term stability of perovskite solar cells is affected by the external environment and internal material composition. Traditional POE packaging films may damage the device at high temperatures, and their additive compatibility, fluidity, adhesion and aging resistance. insufficient.
The polyolefin elastomer (POE) and the polyphonic (PPZ) branches are used for free radical polymerization reactions to prepare the POE-PPZ branch polymer glue film for encapsulation of perovskite photovoltaic batteries. This method reduces layer pressure temperature and gives the film flame retardant performance.
The low -level pressure temperature packaging of the perovskite optical turbine is implemented, the long -term work stability of the device is improved, and the flame retardant performance of the film is enhanced.
Smart Images

Figure CN119351051A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic packaging, and in particular to a method for preparing a flame retardant adhesive film, the flame retardant adhesive film and a method for using the flame retardant adhesive film. Background Art
[0002] Perovskite materials have the characteristics of adjustable band gap, high absorption coefficient, long carrier lifetime and high mobility, which enable perovskite solar cells to show excellent photoelectric conversion efficiency. However, the long-term stability of perovskite solar cells (PSCs) remains the main challenge facing their commercial viability. The stability of perovskite solar cells (PSCs) is jointly affected by external environmental factors such as water, oxygen, light, heat, etc., as well as internal material composition and lattice defects, which lead to cell performance degradation and device decomposition through different mechanisms. Therefore, before the large-scale commercialization of perovskite solar cells, it is urgent to improve their long-term stability. Encapsulation technology can effectively reduce the impact of external factors on the stability of perovskite solar cells. Considering the compatibility with the existing industrialized encapsulation equipment and technology, the application of encapsulation film materials will still be the first choice for comprehensive consideration. However, it is generally believed in the industry that traditional POE encapsulation film is not suitable for perovskite-related optoelectronic devices. The primary reason is that the high temperature (>130 ℃) usually required for its hot pressing may cause irreversible damage to the device. In addition, POE is a non-polar material, and its additive compatibility, fluidity, adhesion and aging resistance need to be further improved to increase the lamination yield and adapt to more stringent actual application environments. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a flame retardant adhesive film, a flame retardant adhesive film and a method for using the flame retardant adhesive film. The flame retardant adhesive film is used for encapsulation of perovskite photovoltaic cells and has the advantages of low lamination temperature and flame retardancy, and can greatly improve the long-term working stability of perovskite photovoltaic devices.
[0004] To achieve the above object, the present invention is implemented by adopting the following technical solutions:
[0005] In one aspect, the present invention provides a method for manufacturing a flame retardant adhesive film, comprising the following steps:
[0006] The polydichlorophosphazene is completely dissolved in an organic solvent, and sodium alcoholate containing unsaturated groups is added to react to obtain polyphosphazene PPZ having unsaturated groups in the side chain; the chemical structure of the polyphosphazene PPZ is:
[0007]
[0008] Wherein, R is selected from one of methyl, ethyl, isopropyl, tert-butyl and phenyl, and n is 30-1000;
[0009] The initiator, the polyolefin elastomer POE particles and the polyphosphazene PPZ are uniformly mixed and reacted to obtain a mixture, and the mixture is processed into POE-PPZ grafted polymer particles;
[0010] The POE-PPZ grafted polymer particles are subjected to extrusion processing to obtain a flame retardant adhesive film.
[0011] Furthermore, the sodium alcoholate containing an unsaturated group is selected from at least one of sodium salt of hydroxyethyl acrylate, sodium salt of hydroxybutyl acrylate, and sodium salt of hydroxypropyl acrylate;
[0012] And / or, the polyolefin elastomer POE particles are selected from at least one of ethylene-propylene copolymer, ethylene-butene copolymer and ethylene-octene copolymer.
[0013] Furthermore, the initiator is selected from at least one of dibenzoyl peroxide BPO, di-tert-butyl peroxide DTBP, and azobisisobutyronitrile AIBN;
[0014] And / or, the organic solvent is selected from one of tetrahydrofuran, acetone, dimethyl carbonate and dioxane.
[0015] Furthermore, the mass ratio of the polydichlorophosphazene to the sodium alcoholate containing an unsaturated group is 1:1.2 to 1:2.5;
[0016] And / or, the initiator, polyolefin elastomer POE particles and polyphosphazene are added in a mass ratio of 5:1 to 20:1;
[0017] And / or, the grafting rate of POE and PPZ grafting is 5% to 33%.
[0018] Furthermore, the initiator, the polyolefin elastomer POE particles and the polyphosphazene are uniformly mixed for reaction, comprising placing the initiator, the polyolefin elastomer POE particles and the polyphosphazene in a three-dimensional motion mixer for mixing for 30-60 minutes, and then placing them for 10-48 hours for reaction.
[0019] Furthermore, the processing of the mixture into POE-PPZ grafted polymer particles comprises sequentially extruding, cooling, air-drying and cutting the mixture to obtain POE-PPZ grafted polymer particles;
[0020] The equipment used for extrusion processing includes a co-rotating twin-screw granulator, the extrusion temperature is 120-150°C, and the screw speed is 120-160 r / min.
[0021] Furthermore, the POE-PPZ grafted polymer particles are subjected to extrusion processing to obtain a flame retardant film, wherein the equipment used for the extrusion processing includes a single-screw extruder, and the extrusion temperature is 80-120°C.
[0022] In a second aspect, the present invention provides a flame retardant adhesive film prepared by the method for manufacturing the flame retardant adhesive film, wherein the lamination temperature of the flame retardant adhesive film does not exceed 90°C.
[0023] In a third aspect, the present invention provides a method for using a flame retardant adhesive film, wherein the flame retardant adhesive film is the flame retardant adhesive film provided by the present invention, or a flame retardant adhesive film prepared by the method for preparing the flame retardant adhesive film provided by the present invention, and the method for using the flame retardant adhesive film comprises the following steps: obtaining the flame retardant adhesive film, cutting and laying it on a pre-prepared perovskite solar cell, and then covering it with a glass cover plate, assembling it, and placing it in a solar module laminator for hot pressing packaging.
[0024] Furthermore, the pressure of the hot pressing packaging is 200-800 mTorr, the temperature is 75-90° C., and the hot pressing time is 5-35 minutes.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention provides a method for preparing a flame-retardant adhesive film, a flame-retardant adhesive film and a method for using the flame-retardant adhesive film. A polyolefin elastomer (POE) and a polyphosphazene (PPZ) are grafted by a free radical polymerization reaction to obtain a POE-PPZ grafted polymer adhesive film. The POE-PPZ grafted polymer adhesive film is used for encapsulating perovskite photovoltaic cells and has the advantages of low lamination temperature and flame retardancy, wherein the lamination temperature can be as low as 75-90°C. The use of the POE-PPZ flame-retardant adhesive film provided by the invention to encapsulate perovskite photovoltaic devices can greatly improve the long-term working stability of the devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the mechanism of POE graft modification for preparing the flame-retardant adhesive film provided in Example 1 of the present invention;
[0028] Figure 2 This is a long-term working stability test diagram of the packaged perovskite battery provided in Example 1 of the present invention; DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0030] In the examples of the present invention, if no specific conditions are specified, all the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained by conventional technical means or purchased commercially.
[0031] Example 1
[0032] This embodiment provides a method for preparing a flame retardant adhesive film and a method for using the same.
[0033] A) Preparation of perovskite cells
[0034] The conductive glass substrate was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen and treated in a UV ozone cleaning machine for 15 min. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150 ℃ hot plate for 45 min to obtain the SnO2 electron transport layer. Equimolar amounts of FAI and PbI2 were dissolved in DMSO to form a perovskite precursor solution with a concentration of 1.4 mol / L. The solution was spin-coated on the substrate at a speed of 3000 r / min for 30 s using a spunbond machine. When the rotation reached 15 seconds, 90 μL of chlorobenzene was dropped on the center of the perovskite substrate. After the rotation, the ITO glass was annealed on a 160 ℃ hot plate for 15 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD doped with Li-TFSI, TBP and FK209Co (III)-TFSI was spin-coated on the perovskite substrate to form a hole transport layer. After spin coating, the substrate is placed in an evaporation device and a 70 nm thick gold film is evaporated on it as the back electrode of the solar cell.
[0035] B) Preparation of POE-PPZ flame retardant film
[0036] In a nitrogen atmosphere, 5.19 g of polydichlorophosphazene was dissolved in 150 ml of tetrahydrofuran, and then 12.42 g (0.09 mol) of sodium hydroxyethyl acrylate was added. After reflux reaction at 65 °C for 48 h, the solvent was removed by rotary evaporation, and the product was poured into 150 ml of petroleum ether for precipitation and washing, and finally vacuum dried to obtain polyhydroxyethyl acrylate-based phosphazene with unsaturated groups in the side chain. According to the formula, appropriate amounts of BPO, polyhydroxyethyl acrylate-based phosphazene and POE particles were weighed and placed in a three-dimensional motion mixer for mixing for 30 min. After mixing evenly, they were allowed to stand for 24 h. The granulator was started and preheated for two hours. The above mixture was put into a co-rotating twin-screw granulator and extruded into a "strip" resin. After the product was cooled in a water bath and dried by a blower, it was cut by a cutting machine to obtain POE-PPZ grafted polymer particles. The extrusion temperature was 120 °C and the screw speed was 120 r / min. The single screw extruder was started and preheated for 1.5 hours. The obtained POE-PPZ grafted polymer particles were dried and placed in the screw extruder to obtain a POE-PPZ film. The extrusion temperature was 95° C. The film was rolled up and packaged for later use.
[0037] C) Use of POE-PPZ flame retardant film
[0038] The POE-PPZ film was cut to the size of the conductive glass substrate, laid on the prepared perovskite solar cell, and then covered with a glass cover. The entire device was placed in a solar module laminator for hot pressing packaging at a pressure of 300mTorr and a temperature of 90°C for 25 minutes. After cooling, the perovskite solar cell encapsulated with the POE-PPZ film was obtained.
[0039] Figure 1 Schematic diagram of the mechanism of POE grafting modification in the examples.
[0040] Example 2
[0041] This embodiment provides a method for preparing a flame retardant adhesive film and a method for using the same.
[0042] A) Preparation of perovskite cells
[0043] The conductive glass substrate was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen and treated in a UV ozone cleaning machine for 20 min. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 180 ℃ hot stage for 30 min to obtain the SnO2 electron transport layer. Equimolar amounts of MAI and PbI2 were dissolved in DMSO to form a perovskite precursor solution with a concentration of 1.5 mol / L. The solution was spin-coated on the substrate at a speed of 4000 r / min for 30 s using a spunbond machine. At the 20th second, 110 μL of chlorobenzene was dropped on the center of the perovskite substrate. After the rotation was completed, the ITO glass was annealed on a 160 ℃ hot stage for 15 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD doped with Li-TFSI, TBP and FK209Co (III)-TFSI was spin-coated on the perovskite substrate to form a hole transport layer. After spin coating, the substrate is placed in an evaporation device and a 70 nm thick gold film is evaporated on it as the back electrode of the solar cell.
[0044] B) Preparation of POE-PPZ flame retardant film
[0045] In a nitrogen atmosphere, 5.19 g of polydichlorophosphazene was dissolved in 150 ml of tetrahydrofuran, followed by the addition of 14.94 g (0.09 mol) of sodium hydroxybutyl acrylate. After reflux reaction at 65 °C for 48 h, the solvent was removed by rotary evaporation, and the product was poured into 150 ml of petroleum ether for precipitation and washing, and finally vacuum dried to obtain polyhydroxybutyl acrylate-based phosphazene with unsaturated groups in the side chain. According to the formula, appropriate amounts of BPO, polyhydroxybutyl acrylate-based phosphazene and POE particles were weighed and placed in a three-dimensional motion mixer for mixing for 45 min. After mixing evenly, the mixture was allowed to stand for 24 h. The granulator was started and preheated for two hours. The mixture was put into a co-rotating twin-screw granulator and extruded into a "strip" resin. After the product was cooled in a water bath and dried by a blower, it was cut by a cutting machine to obtain POE-PPZ grafted polymer particles. The extrusion temperature was 125 °C and the screw speed was 150 r / min. The single screw extruder was started and preheated for 1.5 hours. The obtained POE-PPZ grafted polymer particles were dried and placed in the screw extruder to obtain a POE-PPZ film. The extrusion temperature was 105° C. The film was rolled up and packaged for later use.
[0046] C) Use of POE-PPZ flame retardant film
[0047] The POE-PPZ film was cut to the size of the conductive glass substrate, laid on the prepared perovskite solar cell, and then covered with a glass cover. The entire device was placed in a solar module laminator for hot pressing packaging at a pressure of 320mTorr and a temperature of 85°C for 20 minutes. After cooling, the perovskite solar cell encapsulated with the POE-PPZ film was obtained.
[0048] Example 3
[0049] This embodiment provides a method for preparing a flame retardant adhesive film and a method for using the same.
[0050] A) Preparation of perovskite cells
[0051] The conductive glass substrate was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen and treated in a UV ozone cleaning machine for 25 min. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150 ℃ hot stage for 60 min to obtain the SnO2 electron transport layer. FAPbI3 was dissolved in a mixed solution of DMSO and DMF (the volume ratio of DMSO to DMF was 1:4) to form a uniform solution with a concentration of 1.0 mol / L. The solution was spin-coated on the substrate at a speed of 1000 r / min for 10 s using a gel-spinning machine, and continued to rotate at 4500 r / min for 30 s. At the 20th second, 100 μL of chlorobenzene was dropped into the center of the perovskite substrate. After the rotation, the ITO glass was annealed on a 150 ℃ hot stage for 30 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD doped with Li-TFSI, TBP and FK209Co (III)-TFSI was spin-coated on the perovskite substrate to form a hole transport layer. After spin coating, the substrate was placed in a magnetron sputtering device and a 80 nm silver film was vacuum sputtered as the back electrode.
[0052] B) Preparation of POE-PPZ flame retardant film
[0053] In a nitrogen atmosphere, 5.19 g of polydichlorophosphazene was dissolved in 150 ml of tetrahydrofuran, followed by the addition of 13.52 g (0.09 mol) of sodium hydroxypropyl acrylate. After reflux reaction at 65 °C for 48 h, the solvent was removed by rotary evaporation, and the product was poured into 150 ml of petroleum ether for precipitation and washing, and finally vacuum dried to obtain polyhydroxypropyl acrylate-based phosphazene with unsaturated groups in the side chain. According to the formula, appropriate amounts of BPO, polyhydroxypropyl acrylate-based phosphazene and POE particles were weighed and placed in a three-dimensional motion mixer for mixing for 50 min. After mixing evenly, the mixture was allowed to stand for 24 h. The granulator was started and preheated for two hours, and the above mixture was put into a co-rotating twin-screw granulator for extrusion into a "strip" resin. After the product was cooled in a water bath and dried by a blower, it was cut by a cutting machine to obtain POE-PPZ grafted polymer particles. The extrusion temperature was 145 °C and the screw speed was 150 r / min. The single screw extruder was started and preheated for 1.5 hours. The obtained POE-PPZ grafted polymer particles were dried and placed in the screw extruder to obtain a POE-PPZ film. The extrusion temperature was 102° C. The film was rolled up and packaged for later use.
[0054] C) Use of POE-PPZ flame retardant film
[0055] The POE-PPZ film was cut to the size of the conductive glass substrate, laid on the prepared perovskite solar cell, and then covered with a glass cover. The entire device was placed in a solar module laminator for hot pressing packaging at a pressure of 350mTorr and a temperature of 85°C for 15 minutes. After cooling, the perovskite solar cell encapsulated with the POE-PPZ film was obtained.
[0056] Example 4
[0057] This embodiment provides a method for preparing a flame retardant adhesive film and a method for using the same.
[0058] A) Preparation of perovskite cells
[0059] The conductive glass substrate was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen and treated in a UV ozone cleaning machine for 30 min. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 180 ℃ hot stage for 40 min to obtain the SnO2 electron transport layer. Next, FAPbI3 was dissolved in sulfolane to form a uniform solution with a concentration of 1.3 mol / L, and it was spin-coated on the substrate surface using a spun coater. The spun coater speed was set to 3500 r / min. After spinning for 30 seconds, 80 μl of ethyl acetate was dropped on the center of the perovskite substrate. After continuing to spin-coat at 4000 r / min for 20 seconds, the ITO glass was annealed on a 150 ℃ hot stage for 15 minutes. A chlorobenzene solution of poly (3-hexylthiophene) (P3HT) doped with LiTFSI, TBP and FK209Co (III)-TFSI was spin-coated on the perovskite substrate as a hole transport layer. After spin coating, the substrate was placed in a magnetron sputtering device and a 80 nm silver film was vacuum sputtered as the back electrode.
[0060] B) Preparation of POE-PPZ flame retardant film
[0061] In a nitrogen atmosphere, 5.19 g of polydichlorophosphazene was dissolved in 150 ml of tetrahydrofuran, followed by the addition of 14.94 g (0.09 mol) of sodium hydroxybutyl acrylate. After reflux reaction at 65 °C for 48 h, the solvent was removed by rotary evaporation, and the product was poured into 150 ml of petroleum ether for precipitation and washing, and finally vacuum dried to obtain polyhydroxybutyl acrylate phosphazene with unsaturated groups in the side chain. According to the formula, appropriate amounts of AIBN, polyhydroxybutyl acrylate phosphazene and POE particles were weighed, placed in a three-dimensional motion mixer for mixing for 55 min, and allowed to stand for 24 h after mixing evenly. The granulator was started and preheated for two hours, and the above mixture was put into a co-rotating twin-screw granulator for extrusion into a "strip" resin. After the product was cooled in a water bath and dried by a blower, it was cut by a cutting machine to obtain POE-PPZ grafted polymer particles, with an extrusion temperature of 125 °C and a screw speed of 160 r / min. The single screw extruder was started and preheated for 1.5 hours. The obtained POE-PPZ grafted polymer particles were dried and placed in the screw extruder to obtain a POE-PPZ film. The extrusion temperature was 105° C. The film was rolled up and packaged for later use.
[0062] C) Use of POE-PPZ flame retardant film
[0063] The POE-PPZ film was cut to the size of the conductive glass substrate, laid on the prepared perovskite solar cell, and then covered with a glass cover. The entire device was placed in a solar module laminator for hot pressing packaging at a pressure of 360mTorr and a temperature of 75°C for 25 minutes. After cooling, the perovskite solar cell encapsulated with the POE-PPZ film was obtained.
[0064] Example 5
[0065] This embodiment provides a method for preparing a flame retardant adhesive film and a method for using the same.
[0066] A) Preparation of perovskite cells
[0067] The conductive glass substrate was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 min. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 180 ℃ hot stage for 60 min to obtain the SnO2 electron transport layer. Then, FAI, PbBr2 and CsI were dissolved in a mixed solvent of DMF and DMSO (the volume ratio of DFM to DMSO was 4:1) in an equimolar ratio to form a uniform solution with a total molar amount of 1.6 mol / L, and it was spin-coated on the substrate surface using a spun glue machine. The spun glue machine speed was set to 3000 r / min. When it was turned to 15 seconds, 110 μL of chlorobenzene was dripped into the center of the perovskite substrate. After continuing to spin-coat at 3000 r / min for 15 seconds, the ITO glass was annealed on a 170 ℃ hot stage for 10 minutes to obtain the perovskite light absorption layer. A chlorobenzene solution of poly(3-hexylthiophene) (P3HT) doped with Li-TFSI, TBP and FK209Co (III)-TFSI was spin-coated on the perovskite substrate as a hole transport layer. After spin coating, the substrate was placed in a magnetron sputtering device and a 80 nm silver film was vacuum sputtered as the back electrode.
[0068] B) Preparation of POE-PPZ flame retardant film
[0069] In a nitrogen atmosphere, 5.19 g of polydichlorophosphazene was dissolved in 150 ml of tetrahydrofuran, followed by the addition of 13.52 g (0.09 mol) of sodium hydroxypropyl acrylate. After reflux reaction at 65 °C for 48 h, the solvent was removed by rotary evaporation, and the product was poured into 150 ml of petroleum ether for precipitation and washing, and finally vacuum dried to obtain polyhydroxypropyl acrylate-based phosphazene with unsaturated groups in the side chain. According to the formula, appropriate amounts of DTBP, polyhydroxypropyl acrylate-based phosphazene and POE particles were weighed and placed in a three-dimensional motion mixer for mixing for 50 min. After mixing evenly, the mixture was allowed to stand for 24 h. The granulator was started and preheated for two hours, and the above mixture was put into a co-rotating twin-screw granulator for extrusion into a "strip" resin. After the product was cooled in a water bath and dried by a blower, it was cut by a cutting machine to obtain POE-PPZ grafted polymer particles. The extrusion temperature was 135 °C and the screw speed was 125 r / min. The single screw extruder was started and preheated for 1.5 hours. The obtained POE-PPZ grafted polymer particles were dried and placed in the screw extruder to obtain a POE-PPZ film. The extrusion temperature was 97° C. The film was rolled up and packaged for later use.
[0070] C) Use of POE-PPZ flame retardant film
[0071] The POE-PPZ film was cut to the size of the conductive glass substrate, laid on the prepared perovskite solar cell, and then covered with a glass cover. The entire device was placed in a solar module laminator for hot pressing packaging at a pressure of 400mTorr and a temperature of 85°C for 15 minutes. After cooling, the perovskite solar cell encapsulated with the POE-PPZ film was obtained.
[0072] Comparative Example 1
[0073] This comparative example provides a perovskite battery not encapsulated with a flame-retardant adhesive film. The preparation method of the perovskite battery is the same as that of the perovskite battery provided in Example 1, except that the perovskite battery provided in this comparative example is not encapsulated with a flame-retardant adhesive film.
[0074] The perovskite cells encapsulated with flame retardant films prepared in Examples 1 to 5 were respectively subjected to long-term working stability tests. The test method is as follows: the ambient humidity is controlled at 50%, the cells are allowed to work continuously for 1000 hours in an atmospheric environment and under a standard sunlight illumination, and their photoelectric conversion efficiency is tested by a simulation circuit. The test results are shown in Table 1.
[0075] Table 1 The normalized efficiency of the perovskite cells prepared in Examples 1-5 after working for 1000 hours is uniform
[0076] Normalized efficiency Example 1 87.1% Example 2 88.9% Example 3 89.6% Example 4 86.5% Example 5 90.0%
[0077] Figure 2 This is a long-term working stability test diagram of the encapsulated perovskite battery provided in Example 1 of the present invention, combined with Table 1 and Figure 2 It can be seen that the perovskite cells prepared in Examples 1-5, after being encapsulated with the flame-retardant film, still maintain a relatively high photoelectric conversion efficiency after working for 1000 hours, while the unencapsulated device prepared in Comparative Example 1 fails after working continuously for 24 hours, proving that the flame-retardant film provided by the present invention can greatly improve the long-term working stability of the device.
[0078] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.
Claims
1. A method for manufacturing a flame retardant adhesive film, characterized in that: The following steps are involved: The polydichlorophosphazene is completely dissolved in an organic solvent, and sodium alcoholate containing unsaturated groups is added to react to obtain polyphosphazene PPZ having unsaturated groups in the side chain; the chemical structure of the polyphosphazene PPZ is: Wherein, R is selected from one of methyl, ethyl, isopropyl, tert-butyl and phenyl, and n is 30-1000; The initiator, the polyolefin elastomer POE particles and the polyphosphazene PPZ are uniformly mixed and reacted to obtain a mixture, and the mixture is processed into POE-PPZ grafted polymer particles; The POE-PPZ grafted polymer particles are subjected to extrusion processing to obtain a flame retardant adhesive film.
2. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: The sodium alcoholate containing an unsaturated group is selected from at least one of sodium salt of hydroxyethyl acrylate, sodium salt of hydroxybutyl acrylate, and sodium salt of hydroxypropyl acrylate; And / or, the polyolefin elastomer POE particles are selected from at least one of ethylene-propylene copolymer, ethylene-butene copolymer and ethylene-octene copolymer.
3. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: The initiator is selected from at least one of dibenzoyl peroxide BPO, di-tert-butyl peroxide DTBP, and azobisisobutyronitrile AIBN; And / or, the organic solvent is selected from one of tetrahydrofuran, acetone, dimethyl carbonate and dioxane.
4. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: The mass ratio of the polydichlorophosphazene to the sodium alcoholate containing an unsaturated group is 1:1.2-1:2.5; And / or, the initiator, polyolefin elastomer POE particles and polyphosphazene are added in a mass ratio of 5:1 to 20:1; And / or, the grafting rate of POE and PPZ grafting is 5% to 33%.
5. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: The initiator, the polyolefin elastomer POE particles and the polyphosphazene are mixed uniformly for reaction, comprising placing the initiator, the polyolefin elastomer POE particles and the polyphosphazene in a three-dimensional motion mixer and mixing them for 30-60 minutes, and then placing them for 10-48 hours for reaction.
6. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: Processing the mixture into POE-PPZ grafted polymer particles comprises sequentially extruding, cooling, air-drying and cutting the mixture to obtain POE-PPZ grafted polymer particles; The equipment used for extrusion processing includes a co-rotating twin-screw granulator, the extrusion temperature is 120-150°C, and the screw speed is 120-160 r / min.
7. The method for manufacturing a flame retardant adhesive film according to claim 1, characterized in that: The POE-PPZ grafted polymer particles are subjected to extrusion processing to obtain a flame retardant film, wherein the equipment used for the extrusion processing includes a single-screw extruder, and the extrusion temperature is 80-120°C.
8. A flame retardant adhesive film prepared by the method for preparing a flame retardant adhesive film according to any one of claims 1 to 7, characterized in that: The lamination temperature of the flame retardant adhesive film does not exceed 90°C.
9. A method for using a flame retardant adhesive film, wherein the flame retardant adhesive film is a flame retardant adhesive film prepared by the method for preparing a flame retardant adhesive film according to any one of claims 1 to 7, or a flame retardant adhesive film according to claim 8, characterized in that: The following steps are involved: Obtain a flame-retardant adhesive film, cut it and lay it on the pre-prepared perovskite solar cell, then cover it with a glass cover plate, assemble it and put it into a solar module laminator for hot pressing packaging.
10. The method for using the flame retardant adhesive film according to claim 9, characterized in that: The pressure of the hot pressing packaging is 200-800 mTorr, the temperature is 75-90° C., and the hot pressing time is 5-35 minutes.
Citation Information
Patent Citations
Carboxyl or sulfo group terminated polyethylene grafted phosphonitrile compound and hydrogel patch
CN107522802A
Photovoltaic single-component transparent silicone structural sealant and preparation method thereof
CN115260981A
Curable phosphazene compound, its production and cured body thereof
JP1993286988A
Polyphosphazene polymers
US6392008B1